Society needs to take lead in fight against school violence - Abd Razak, Dzulkifli (2004)
THE fundamental tenet of basic education is generally summed up as the 3Rs — reading, (w)riting and (a)rithmetic. In some countries however, the 3Rs have come to represent "revolvers, rifles and repeaters" — a frightening reflection of how schools can be a playground for crimes. Although the situation in Malaysia is still under control, of late, it is getting more worrying. The local version of 3Rs is fast changing to mean "rascals, rogues and ruffians." The latest tragic episode involving the death of a pupil in a religious school is a case in point; another testimony of how bad the situation can be.